MIPS - Mapping the Relationship between Research, Innovation, and Society through Topic Modeling - Nolasco, Diogo; Oliveira, Jonice (Anais Estendidos do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
The proliferation of scientific data on the internet, including social networks, blogs, patents and articles, demands integrated analysis to guide strategic decisions. This data covers the life cycle of innovation, from scientific publications, through patents, to public perception of innovations. Understanding these dimensions allows you to better allocate resources and efforts in strategic areas that are well received by society. Although initiatives like Altimetry evaluate the specific impact of articles or authors, there is a gap in analyzing the interrelationships between ideas, discoveries, products and opinions over time. In this context, topic modeling emerges as a powerful tool for extracting and understanding themes in textual data. This work proposes an integrated technique to identify and analyze topics and their relationships in the scientific, technological and social spheres. The solution allows you to cross topics of different dimensions, revealing how an innovation is born, grows, turns into a commercial product and is perceived by society. Unlike current solutions that focus on a single dimension, this method offers a multidimensional view. The experiments carried out show the growth of research topics over time and how they were discussed by society, in addition to relating rumors and misinformation. The results indicate significant connections between the dimensions studied, highlighting the relationship of topics with milestones in the evolution of innovation. In the future, experiments will be conducted involving all three dimensions (science, technology and society), accompanied by the creation of visualizations to facilitate technological prospecting.